Pengaruh Pemberian Berbagai Bahan Zat Pengatur Tumbuh Alami Pada Pertumbuhan Bibit Cempedak (Artocarpus champeden Lour.) - Ganitha Kamillia; Ellok Dwi Sulichantini; Penny Pujowati (Jurnal Agroekoteknologi Tropika Lembab, 2019)
The use of coconut water, green bean sprouts and onions is chosen as natural growth regulator because it is easily obtained at a fairly affordable price. The aim of the study was to determine the effect of various natural growth regulator different concentrations to the growth of cempedak (Artocarpus champeden Lour.) seedlings.The research was conducted from May to July 2018 in the garden of the Tissue Culture Laboratory Faculty of Agriculture, Mulawarman University. This study used a factorial Completely Randomized Design with five replications. The first factor was the types of growth regulator, namely: coconut water, green bean sprout extract, and onion extract. The second factor was the concentration of the natural growth regulator substances,consisted of five treatment levels, namely: 0, 25, 50, 75 and 100 mL L-1. The parameters observed were plant height, number of leaves, stem diameter, root length, fresh weight (leaves, stems and roots), dry weight (leaves, stems and roots) and leaf area. Data were analyzed by analysis of variance with F-test and continued with the Least Significant Difference (LSD) test with a level of 5%. The results showed that there was no interaction between the type and concentration level of the natural growth regulator to the growth of cempedak seedlings.The growth regulator concentrationalso had no significant effect to all growth parameters observed. However, of the type of natural growth regulators showed a significant in the fresh root weight,stem dry weight, and plant height at harvest time.